2016
DOI: 10.1080/02813432.2016.1249060
|View full text |Cite
|
Sign up to set email alerts
|

History of violence and subjective health of mother and child

Abstract: ObjectiveTo study the self-reported prevalence of experienced violence among a cohort of women about two years after giving birth, their health during pregnancy, pregnancy outcomes and their experience of their child’s health.Setting and subjectsIn 2011, a total of 657 women participated in phase III of the Childbirth and Health Cohort Study in Icelandic Primary Health Care, 18 to 24 months after delivery. The women had previously participated in phase I around pregnancy week 16 and phase II 5–6 months after d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
4
11
0
Order By: Relevance
“…In line with previous studies, women with a history of violence were also at an increased risk of a premature birth before 37 week of gestation. Tomasdóttir et al [37] also reported that women with a history of violence were at an increased risk of a CS, however Tomasdóttir did not report on whether the CS was an emergency or planned. BIDENS large cohort study which was conducted in six European countries demonstrated the risk of a planned CS for nonobstetrical reasons in primiparous women who had experienced sexual abuse as an adult was high when compared with women who had not experienced sexual violence [24].…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies, women with a history of violence were also at an increased risk of a premature birth before 37 week of gestation. Tomasdóttir et al [37] also reported that women with a history of violence were at an increased risk of a CS, however Tomasdóttir did not report on whether the CS was an emergency or planned. BIDENS large cohort study which was conducted in six European countries demonstrated the risk of a planned CS for nonobstetrical reasons in primiparous women who had experienced sexual abuse as an adult was high when compared with women who had not experienced sexual violence [24].…”
Section: Discussionmentioning
confidence: 99%
“…Increased operative interventions have also been associated with DV. Women exposed to DV are at increased risk of giving birth by Cesarean Section (CS) according to European studies [17, 18]. Women reporting current suffering from adult sexual abuse had the highest risk of an elective CS [17].…”
Section: Introductionmentioning
confidence: 99%
“…The findings from this study around an increased risk of a CS in women with a history of violence is in line with other international studies. Tomasdóttir et al [35] reported that women with a history of violence were at an increased risk of giving birth by CS, however their results did not report whether the CS an emergency or planned CS. In 2017, the proportion of planned CS births in Sweden 9.4 %, which is a higher percentage than reported in the present study.…”
Section: Discussionmentioning
confidence: 90%